DEVELOPMENT OF KOKAI SUGAR LEARNING MEDIA "GAME OF LADDER SNAKE AND MAGIC BOX" FOR CLASS XI HIGH SCHOOL - Rika Dewi; Ida Putri Rarasati (JOSAR (Journal of Students Academic Research), 2020)
Abstract: This research is motivated by the lack of effective learning in SMAN l Kademangan which is still conventional. Through learning media students are given convenience in understanding learning material. Media Kokai Sugar is an appropriate learning media to be used as a variation of learning in PPKn learning. This study aims to develop the Kokai Sugar Media “Game of Snake Ladder and Magic Box” for high school class XI. The research method used in this study is the R & D development model by Sugiyono. The subjects of this study were material experts, media experts, linguists, and 28 students of class XI IPA 2 of SMAN 1 Kademangan who had received material about the harmonization of human rights and obligations in the perspective of the Pancasila. The instruments of data collection in this study used material expert validation sheets, media expert validation sheets, language expert validation sheets, and student response questionnaires. The study produced a learning media in the form of Kokai Sugar “A Game of Snake Ladder and Magic Box.” After the revision, Kokai Sugar was included in the feasible category from the results of material validation with an average value of 3.21, media validation with an average value of 4.2, and language validation with an average value of 4.1. Thus, Kokai Sugar is worthy of being used as a learning medium in improving PPKn learning outcomes.